2020
DOI: 10.2147/dmso.s230684
|View full text |Cite
|
Sign up to set email alerts
|

<p>Endothelial Function in Obese Patients Treated with Bariatric Surgery</p>

Abstract: Bariatric surgery (BS) is becoming an increasingly frequent treatment option especially in people with morbid obesity, demonstrating that it is able to reduce total mortality and cardiovascular (CV) risk. Despite endothelial dysfunction is an essential requisite contributing to atherosclerosis and predicting CV events, only some studies have investigated the effects of BS on endothelial function with controversial results. In this study, the effects of weight loss on endothelial function were investigated in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Borzi et al suggested that a slight but significant increase in cardiovascular events occurs in the first months following surgery, when compared with a non-surgical control group [ 17 ]. However, because cardiovascular events follow vascular disease progression that develop over time, it is also reasonable to assume that reducing obesity-related risk factors will also reflect in a reduction in cardiovascular events over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borzi et al suggested that a slight but significant increase in cardiovascular events occurs in the first months following surgery, when compared with a non-surgical control group [ 17 ]. However, because cardiovascular events follow vascular disease progression that develop over time, it is also reasonable to assume that reducing obesity-related risk factors will also reflect in a reduction in cardiovascular events over time.…”
Section: Discussionmentioning
confidence: 99%
“…Differential arterial responses to weight reduction surgery have been reported based on metabolic status, highlighting heterogeneity in physiological responses to weight loss and changes in adiposity, and probable activation of separate pathways in clinical subgroups [ 16 ]. However, FMD responses following bariatric surgery may be unchanged [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first time that a decrease in leukocyte activation and endothelial dysfunction after bariatric surgery has been demonstrated by means of a dynamic system in which an in vivo blood flow is simulated and interaction with endothelial cells can be visualised. Previous studies investigating classic functional and structural markers of early atherosclerosis, such as flow-mediated dilation and carotid artery intima-media thickness, have provided inconsistent results concerning the effects of bariatric surgery on endothelial function [19,42]. Indeed, the mechanisms involved in the early asymptomatic stages of atherosclerosis can be triggered many years before clinical signs are manifested [7], thus suggesting that a leukocyte-endothelial cell interaction-based approach would be useful for early detention of subclinical atherosclerosis risk.…”
Section: Discussionmentioning
confidence: 99%
“…In cohort studies, although most of the selected studies [ 16 , 32 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] showed representativeness of the cases, the majority of them were distinguished by a lack of nonexposed group definition information. Since most of the studies did not include a control group, they were not assessed for comparability.…”
Section: Resultsmentioning
confidence: 99%
“… ( A ) Forest plot displaying standardized mean difference and 95% confidence intervals showing the consequence of bariatric surgery on IMT [ 16 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]; ( B ) Leave-one-out sensitivity analyses indicating the effect of bariatric surgery on IMT [ 16 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , …”
Section: Figurementioning
confidence: 99%